MEKANISME “HUTANG MUSIM” MENURUT HUKUM ISLAM DAN KITAB UNDANG UNDANG HUKUM PERDATA - Novia Herawanti; Muhammad Torik; Armasito Armasito (Muqaranah, 2021)
Abstract There are still many people who practice seasonal debt in Pelang Kenidai Village, Dempo Tengah District, Pagar Alam City, but do not know the legal basis and origin of the practice from the side of Sharia or Islamic law, therefore this study intends to help understand the phenomena that occur in the community and draw conclusions from what has been obtained from field monitoring. The question that the author wants to answer from this research is the mechanism of seasonal debt according to Islam that occurred in Pelang Kenidai Village, Dempo Tengah District, Pagar Alam City. The method that the author uses in this research is Field Research. The data that the author uses is primary data, namely data obtained through existing data in the field or data directly obtained from correspondents. The author analyzed the data using quantitative descriptive methods. The result that the author got is that the practice of debt this season has several things that are in line with and not in line with Islamic law, one example is at the time of the initial contract it must get the approval of both parties and what is not in line is the interest on the loan which has no basis and is only a the customs of the surrounding community so that Al Urf or the rules Al-Adatu Muhakkamah apply in this subject. Keywords: Seasonal Debt, Islamic Law, Customs.